Additional Criminal Impositions in Corruption Crimes - Silalahi, Jhonryan Samta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The crime of corruption is one of the criminal offenses and unlawful acts committed by a person or corporation with the aim of benefiting themselves or corporations, by abusing the authority, opportunity or means attached to their position and having an impact on state losses. Additional punishment in the crime of corruption is given by the judge because the convict has committed an extraordinary crime. The imposition of additional punishment in the crime of corruption is facultative where this additional punishment can only be imposed together with the main punishment. The judge is not required to impose additional punishment (the judge may choose). Deprivation of certain rights, forfeiture of certain goods, and announcement of the judge's decision are additional punishments given by the judge.